1996
DOI: 10.1007/bf02895288
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of adjustment, activity, and tangible social support in men and women patients and their spouses during the six months post-myocardial infarction

Abstract: A longitudinal study was conducted to investigate gender differences in adaptation and activity among survivors of acute myocardial infarction (MI) and their spouses during the six months post-hospital discharge. Male and female married survivors of MI, matched on age, disease severity, and socioeconomic status, and their spouses responded to measures about functional impairment, psychological distress, and level of involvement in household and other activities prior to and 4, 10, 16, and 22 weeks after the MI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 32 publications
3
21
0
1
Order By: Relevance
“…For both men and women, social support (measured as being married) has been shown to be an independent predictor for survival rates and recurrent infarction in CAD patients (Chandra et al 1983;Williams et al 1992). However, women with CAD tended to report lesser informational, instrumental and emotional support than men (Hildingh and Fridlund 1997;Rose et al 1996).…”
Section: Psychosocial Cardiac Risk Factorsmentioning
confidence: 95%
“…For both men and women, social support (measured as being married) has been shown to be an independent predictor for survival rates and recurrent infarction in CAD patients (Chandra et al 1983;Williams et al 1992). However, women with CAD tended to report lesser informational, instrumental and emotional support than men (Hildingh and Fridlund 1997;Rose et al 1996).…”
Section: Psychosocial Cardiac Risk Factorsmentioning
confidence: 95%
“…Rose et al (1996) showed that female patients, soon after a heart attack, worked more hours in the household than their husbands, whereas in contrast, male patients experienced a significant relief by their spouses from household duties in the weeks after their heart attack. Artinian and Duggan (1995) and King, Porter, and Rowe (1994) assessed the subjective stress of patients after a bypass surgery on a continuous scale and showed that women also felt more restricted by their household chores than men.…”
Section: Discussionmentioning
confidence: 93%
“…Psychosocial factors and social support contribute to the recovery process (e.g., Barry, Kasl, Lichtman, Vaccarino, & Krumholz, 2006;Elizur & Hirsh, 1999) and may partially account for gender differences (Logsdon, Usui, Cronin, & Miracle, 1998). In particular, some authors have suggested that women's traditional role demands might affect recovery after CABG Lemos, Suls, Jenson, Lounsbury, & Gordon, 2003;Rose, Suls, & Green, 1996). Especially in the early phase of recovery, when patients are instructed to avoid exertion of the upper part of the body, traditionally female domestic activities such as vacuuming and washing dishes could increase the risk for complications , mask cardiac symptoms , and divert attention from the patient's own needs (Helgeson, 1993).…”
Section: Introductionmentioning
confidence: 98%
“…Four available studies reported higher depression scores for women than men (Conn, Taylor, & Abele, 1991;Frasure-Smith et al, 1999;Schleifer et al, 1989;Stern et al, 1977), while other studies report no gender differences (Crowe et al, 1996;Riegel & Gocka, 1995;Rose et al, 1996;Wiklund et al, 1993). For both men and women, major depression following AMI has not been documented.…”
Section: Literature Reviewmentioning
confidence: 85%